The Language Tourism as a comprehensive and sectoral development strategy - Guanilo Aranda, Elsa (2021)
The aim of this study is to evidence the role of the language tourism as a comprehensive and sectoral development strategy so that it becomes the force to create work, to encourage production, to promote trade. This research demonstrated that the intercultural aspects management is a key element for an appropriate work group integration since national and cultural identity respect, cosmovision and universal values must be always emphasized. It was concluded that language tourism impacts positively the quality of life and improves different regions where this activity takes place. The language tourism implies not only the academic service offered by language specialists as institutions and universities representatives but also complementary tourism services and products to fulfil this type of tourism. All this in the framework of the Sustainable Development Goals. Then, Language Tourism must be part of a roadmap of the government plans of the countries with a great academic and cultural potential.